Pendekatan Anestesi pada Kraniotomi Retromastoid pada Pasien Tumor Cerebellopontine Angle Disertai Hidrosefalus dan Malfungsi Ventriculoperitoneal Shunt - I Made Banu Pati; Ida Bagus Krisna Jaya Sutawan (Universitas Malahayati, 2026)
ABSTRACT Cerebellopontine angle (CPA) tumors are complex intracranial lesions involving critical neurovascular structures and are frequently associated with increased intracranial pressure, hydrocephalus, cranial nerve dysfunction, and perioperative anesthetic challenges. This case report aimed to describe anesthetic management in retromastoid craniotomy for a CPA tumor with hydrocephalus and ventriculoperitoneal (VP) shunt malfunction. This article was prepared as a clinical case report based on anamnesis, physical examination, laboratory and radiologic findings, perioperative anesthetic management, intraoperative monitoring, and postoperative intensive care. A 57-year-old male with a left CPA tumor, acute communicating hydrocephalus due to proximal VP shunt malfunction, and symptomatic epilepsy underwent tumor removal through retromastoid craniotomy in the parkbench position using intraoperative neurophysiological monitoring. Anesthesia was conducted with total intravenous anesthesia using target-controlled infusion of propofol and remifentanil, invasive arterial and central venous monitoring, scalp block, controlled ventilation, mannitol, and multimodal analgesia. Intraoperatively, hemodynamics remained stable, with blood pressure 100-150/70-90 mmHg, heart rate 60-82 beats/minute, SpO2 99-100%, blood loss 900 mL, and urine output 1.9 mL/kg/hour. The frozen section finding was consistent with dermoid cyst. The patient was transferred to the intensive care unit with retained intubation, extubated on postoperative day one, transferred to the ward on day three, and discharged on postoperative day seven. Comprehensive neuroanesthetic management, TIVA-based IONM support, parkbench-position risk anticipation, intracranial pressure control, and systematic postoperative intensive care are essential to optimize outcomes in complex CPA tumor surgery. Keywords: Cerebellopontine Angle, IONM, Neuroanesthesia, Parkbench Position, TIVA. ABSTRAK Tumor cerebellopontine angle (CPA) merupakan lesi intrakranial kompleks yang melibatkan struktur neurovaskular vital dan sering berkaitan dengan peningkatan tekanan intrakranial, hidrosefalus, disfungsi saraf kranialis, serta tantangan anestesi perioperatif. Laporan kasus ini bertujuan untuk mendeskripsikan manajemen anestesi pada kraniotomi retromastoid pasien tumor CPA disertai hidrosefalus dan malfungsi ventriculoperitoneal (VP) shunt. Artikel ini disusun sebagai laporan kasus klinis berdasarkan anamnesis, pemeriksaan fisik, pemeriksaan laboratorium dan radiologi, manajemen anestesi perioperatif, monitoring intraoperatif, serta perawatan intensif pascaoperasi. Seorang laki-laki usia 57 tahun dengan tumor CPA sinistra, hidrosefalus komunikans akut akibat malfungsi VP shunt proksimal, dan epilepsi simptomatik menjalani pengangkatan tumor melalui kraniotomi retromastoid dalam posisi parkbench menggunakan intraoperative neurophysiological monitoring. Manajemen anestesi dilakukan dengan total intravenous anesthesia berbasis target-controlled infusion propofol dan remifentanil, pemantauan invasif arterial line dan central venous catheter, scalp block, ventilasi terkontrol, pemberian manitol, serta analgesia multimodal. Selama intraoperatif, hemodinamik stabil dengan tekanan darah 100-150/70-90 mmHg, heart rate 60-82 kali/menit, SpO2 99-100%, perdarahan 900 mL, dan urine output 1,9 mL/kgBB/jam. Hasil frozen section sesuai dermoid cyst. Pasien dipindahkan ke ICU dengan retained tube intubation, berhasil diekstubasi pada hari pertama pascaoperasi, pindah ke ruangan pada hari ketiga, dan pulang pada hari ketujuh pascaoperasi. Kesimpulan: Manajemen neuroanestesi komprehensif, dukungan IONM berbasis TIVA, antisipasi risiko posisi parkbench, kontrol tekanan intrakranial, serta perawatan intensif pascaoperasi yang sistematis berperan penting dalam optimalisasi luaran pasien pada pembedahan tumor CPA kompleks. Kata Kunci: Cerebellopontine Angle, IONM, Neuroanesthesia, Posisi Parkbench, TIVA.